Taxonomical Approaches of TV Genre and Formats in the Age of Intermediality - حسین, کۆڤان حسین سعدو; اسماعیل, ا.د.ابتسام اسماعیل قادر (Sulaimani Journal for Humanities, 2025)
There are only two main approaches to classifying television content: either by format or genre. These two approaches interpret and classify programs according to subject, visual elements, target audience, and production mood. The evolution of the media ecosystem and the adaptation of media species to the new conditions affect the dominant traditional TV genre and format. Due to these simulation processes, new genres emerge from media convergences, and traditional genres adapt to new generic characteristics. Hence, television format functions as a recipe consisting of how-to-make distinctive elements of television programming, which considers another catalyst. This paper tries to reevaluate the taxonomies of TV program categorization, aiming to go beyond the traditional genres of television programs. In the age of intermobility, genre conventions have changed, and TV genres develop and transform into new formulas. This paper critically analyses a body of TV programs to discover the major changes in the genre and format of Kurdish television, sampling the Kurd sat channel program over the past 21 years. The paper concludes that Kurdish channels are saturated with traditional genres, in particular conversational-based genres therefore failed to adapt to new genres and global TV formats.
Keywords: Genre; Format; content taxonomy; TV program; intermobility